Penerapan Metode Quality Function Deployment dan Antropometri dalam Perancangan Desain Mesin Cacah Sampah Organik dan Non Organik - Navik Kholili; Astria Hindratmo; Alfi Nugroho (Journal of Research and Technology, 2021)
The Garbage is residual material that has been disposed of and is no longer used, so that waste is considered something disgusting by some people. Garbage has two types, namely organic waste and inorganic waste. Therefore, good waste management is needed so that every day waste does not accumulate and does not disturb the surrounding environment. The purpose of this research is to design a garbage chopper that is useful for chopping organic and inorganic waste to help the waste processing process so that there is no buildup every day. The design of this chopping machine is made multi-functional that can chop organic or inorganic types of waste, designed according to the wishes of consumers or users and made ergonomically. The method used in this research is the Quality Function Deployment (QFD) method and the user's body Anthropometry so that the dimensions of the machine are in accordance with the user which causes the design to be ergonomic. The results of the research are to produce a design of organic and inorganic waste chopping machines that have specifications such as machines using mild steel so that they are easy to move, durable, speed up the chopping process because there is a speed setting, automatic. In addition, the machine has ergonomic dimensions from the results of the machine user's body measurements using the anthropometric method.